Lethal haemorrhage due to erosion of external iliac artery in a patient with ureterovaginal fistula following endometriosis surgery. Issue 4 (December 2019) - Widschwendter, Peter; Janni, Wolfgang; Benckendorff, Julian; de Gregorio, Nikolaus
We present a case report of a patient with laparoscopic surgery of a deep infiltrating endometriosis with a complicative course. In addition to a postoperatively diagnosed ureteral fistula with local inflammation, acute perforation and ultimately lethal bleeding from the adjacent external iliac artery occurred more than 3 weeks after surgery. To the best of our knowledge, a case with the same constellation has not yet been published. A literature review on the rare and comparable complication of a ureteroarterial fistula is discussed in connection with the case.